Vocational education and training - a stepping stone to successful career pathways - Ertl, Hubert [Verfasser] (My University, 2019)
"This part looks at transitions at the so-called 'second threshold', i.e. transitions from initial training to working life. This threshold is certainly a valid object of debate in itself. VET research into the consequences of digitalisation has shown that change processes are gaining in momentum and that new requirements are constantly bringing about realignments in people’s working lives. The articles included here also take account of this development." (Author's abstract ; BIBB-Doku)
Berufliche Bildung – Sprungbrett für erfolgreiche berufliche Karrierewege
Keywords: G 1.3.2.2 Übergänge; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.3.4 Qualifikationswandel; Berufseinmündung; Zweite Schwelle; Qualifikationswandel